2-Deoxyglucose protects hippocampal neurons against kainate-induced temporal lobe epilepsy by modulating monocyte-derived macrophages (mo-MΦ) and progranulin production in the hippocampus. (August 2019) - Nikbakht, Farnaz; Belali, Rafie; Rasoolijazi, Homa; Mohammad khanizadeh, Ali
Abstract: Inflammation is an important factor in the pathology of epilepsy with the hallmarks of resident microglia activation and infiltration of circulating monocytes in the damaged area. In the case of recovery and tissue repair, some monocytes change to macrophages (mo-MΦ) to enhance tissue repair. 2-deoxyglucose (2DG) is an analog of glucose capable of protecting the brain, and progranulin is a neurotrophic factor produced mainly by microglia and has an inflammation modulator effect. This study attempted to evaluate if one of the neuroprotective mechanisms of 2-DG is comprised of increasing monocyte-derived macrophages (mo-MΦ) and progranulin production. Status epilepticus (SE) was induced by i.c.v. injection of kainic acid (KA).2DG (125/mg/kg/day) was administered intraperitoneally. Four days later, animals were sacrificed. Their brain sections were then stained with Cresyl violet and Fluoro-Jade B to count the number of necrotic and degenerating neurons in CA3 and Hilus of dentate gyrus of the hippocampus. Lastly, immunohistochemistry was used to detect CD11b + monocyte, macrophage cells, and Progranulin level was evaluated by Western blotting. The histological analysis showed that 2DG can reduce the number of necrotic and degenerating neurons in CA3 and Hilar areas. Following KA administration, a great number of cD11b + cells with monocyte morphology were observed in the hippocampus. 2DG not only reduced cD11b + monocyte cells but was able to convert them to cells with the morphology of macrophages (mo-MΦ). 2DG also caused a significant increase in progranulin level in the hippocampus. Because macrophages and microglia are the most important sources of progranulin, it appears that 2DG caused the derivation of monocytes to macrophages and these cells produced progranulin with a subsequent anti-inflammation effect. In summary, it was concluded that 2DG is neuroprotective and probably one of its neuroprotective mechanisms is by modulating monocyte-derived macrophages by progranulin production. Highlights: Higher number of cD11b + cells with monocyte morphology was observed in the hippocampus after KA-induced status epilepticus. 2-DG alleviates necrotic and degenerating neurons in CA3 and Hilar areas. 2- DG converts the infiltrated monocytes to monocyte-derived macrophages (mo-MΦ) probably by inducing progranulin production. Mo-MΦ are responsible for tissue repair in the brain.